If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(y) + 4xy + 3 = 0 Multiply x * y xy + 4xy + 3 = 0 Reorder the terms: 3 + xy + 4xy = 0 Combine like terms: xy + 4xy = 5xy 3 + 5xy = 0 Solving 3 + 5xy = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 5xy = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 5xy = 0 + -3 5xy = 0 + -3 Combine like terms: 0 + -3 = -3 5xy = -3 Divide each side by '5y'. x = -0.6y-1 Simplifying x = -0.6y-1
| x(x)+4x+3=0 | | 2x+13=76+5x | | x+y=x(x) | | x+x=x+x | | (x)(y)(x+1)(y+1)=1 | | (x)(x)(x)(x)(x)(x)(x)(x)(x)(x)(x)(x)(x)=1 | | x(x)(x)=1 | | 2t^2+21t+52=0 | | 15-2(x+3)=x+9 | | 7(x+7)=2x-1 | | 29+x=7x+5 | | 13-(-2x+5)=8 | | 6+10=416 | | 4t^3-4t=0 | | x(x-28)=-196 | | y=-1/2x+8 | | 4x+13=57 | | 7ln(4x)=28 | | 8y-28=3y+2 | | -1/2x+8=1x+2 | | x-3=x^2 | | (x+8)(x^2+7x-18)=0 | | 16-(x-8)=0.85-20 | | 5c+8=4c+15 | | (1/2x+x)+(x+5)=100 | | 0.5*x+x+x+5=100 | | 7-z/3z=-1/6 | | 3(5+x+1)= | | 15+3x+3= | | 1/5+1/6*1/3 | | 2x-(2/3)(x-2)=1/3(x-0.5(3x+1)) | | 5x-6-(5x+6/4)=1 |